26. Best Practices in Online Conference Moderation - De Schutter, Adrienne; Fahrni, Patricia; Rudolph, Jim (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
Facilitation by a moderator is crucial to a purposeful and productive conference. The moderator keeps the session focused, and ensures that all participants receive feedback regarding their contributions to the discussion. These functions are particularly important in the otherwise impersonal context of online discussion. The current report reviews recent literature regarding the moderator’s roles regarding participant access and motivation, online socialization, information exchange and knowledge construction. A synchronous audio conference situation is assumed. Principles of online teaching and learning identified by Salmon (2002) are discussed, as well as the direct personal experiences of the report’s co-authors.